PEMANFAATAN KOMPOS DAN PHONSKA PLUS PADA LAHAN KERING MASAM TERHADAP PERTUMBUHAN, DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L) DI KABUPATEN MINAHASA - Joice.M.J. Supit; Y.E.B. Kamagi; L.Th. Karamoy (COCOS, 2022)
ABSTRACTField Experiments on "Utilization of Compost and Phonska Plus in Acid Dry Land Against Growth, and Production of Shallots (Allium ascalonicum L.) in Minahasa Regency". While the objectives to be achieved in this study are a) Increasing the use of acid dry lands for activity of product agriculture; b) Determine the optimal compost and phonska plus dosage for agricultural business; c) Improve soil physical properties, soil chemistry and soil biology for acid dry lands to become productive land for agricultural business; f) Comparing the use of compost using phonska plus and non-phonska plus. The research was conducted in a field experiment by analyzing compost and soil in acid dry land before and after dolomite, phonska plus and compost treatment. The dolomite dosage 13,335 tonnes/ha (4 kg/3m2) for all pot. The compost dosage treatment consisted of Ko = 0 tonnes / ha (0 kg / 3 m2) as a control, K1= 15 tonnes / ha (2.7 kg / 3m2); K2= 30 tonnes / ha (5.4 kg / 3m2); K3 = 45 tonnes / ha (8.1 kg / 3 m2) and K4 = 60 tonnes / ha (10.8 kg / 3m2). The phonska plus treatment consisted of Po = 0 kg/ha (0 gr/ 3 m2) ; P1 = 400 kg/ha (120 gr/ 3 m2); P2 = 800 kg/ha (240 gr/ 3 m2); P3 = 1.200 kg/ ha (360 gr/ 3 m2). Onion plants as an indicator. Size of the plot / plot 2 m x 1.5 m (3 m2). Research time for 8 months. The research method was a factorial experiment with a randomized block design (RBD) and 3 replications. Statistical testing for tabulated data used Analysis of Variance (ANOVA) and Least Significant Difference Test Analysis (LSD). The results of the study showed that compost and phonska plus treatment had a significant effect on the growth and production of shallot plants. The dosage optimum of Phonska Plus treatment of 1.200 kg/ha and Compost treatment of 45 tons / ha provides maximum growth and production of shallots. Key words: Compose, Phonska Plus, Acid Dry Land, Shallots